Trends in Social Media Use among University Students During the Covid-19 Pandemic - Mohd Najib, Mohd Nadzri; Izani Othman, Mohd; Sulaiman, Suraya; Ernestina Tenda, Priska; Azrul Zabidi, Muhammad (International Journal of Academic Research in Progressive Education and Development, 2023)
Background: The COVID-19 pandemic has led to an increase in social media usage among teens and young adults which may be helpful or harmful. This study aimed to investigate the use of social media and trends among diploma in pharmacy students at UiTM Cawangan Pulau Pinang, Kampus Bertam. Method: A cross‑sectional study was conducted whereby data was collected through an online survey and completed questionnaires by 189 respondents (18-22 years old) undertaking diploma in pharmacy in and off campus. Data were analysed using Microsoft Excel Spreadsheet for descriptive statistics and frequency analysis. SPSS version 28.0 was used to analyse the inferential statistics i.e. the Kruskal-Wallis test.Results: The analysis of the collected data revealed that the majority of the respondents were female and considered themselves moderate users of social media, with an average of four social media accounts. The study also found that social media consumption among pharmacy students at UiTM Cawangan Pulau Pinang increased during the pandemic compared to the average time spent before. The data showed that a significant percentage of students spend several hours on social media, with the most commonly reported problems being distraction from studying and addiction. These findings raise concerns about the negative effects of social media usage on academic performance and well-being. Conclusion: Overall, the study provides valuable insight into the habits and exposure of students to social media usage, highlighting the need for further research and awareness of the potential risks associated with excessive social media consumption.